A democracia mutualista - Proudhon, Pierre-Joseph (Ecopolítica, 2018)
Pierre-Joseph Proudhon. “Democracia mutualista” in Proudhon. Orgs. Paulo- Edgar A. Resende e Edson Passetti. Editora: Ática. São Paulo, 1986.